Razumevanje moškosti med srednješolsko mladino v Sloveniji - Mikić, Jasna (Teorija in praksa, 2025)
The topic of men/masculinity has received considerable attention worldwide, albeit not so much in Slovenia. After conducting a pilot study to directly measure Slovenian high school youth’s perceptions of masculinities, we established that their perceptions are based strongly on Western hegemonic models of masculinity that stress the image of a strong, competitive, fearless man who must f inancially provide for his family, is not allowed to show feelings or seek help, and is expected to frequently change sexual partners and solve problems violently. The study provides important insights into masculinity in the Slovenian context and is an useful starting point for further research on this topic.
Keywords: Mladina; Moškost; Stereotipi (socialna psihologija); Študije spolov